2014
DOI: 10.1002/ejp.597
|View full text |Cite
|
Sign up to set email alerts
|

Attentional bias for pain‐ and period‐related symptom words in healthy women who experienced a recent painful period

Abstract: Pain-related attentional biases are associated with recent menstrual pain severity. The experience and severity of pain, rather than its duration (i.e., whether pain is chronic or acute), may be the primary determinants of pain-related attentional bias. Future research could explore attentional biases in acute clinical pain samples to confirm this notion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Yet, research has shown that skinrelated disgust plays a role for patients with chronic skin diseases, so a relationship between attention to itch and disgust seems plausible [49] Nevertheless, the cumulative evidence for a preconscious AB towards-or avoidance of threat related stimuli like itch or pain is limited. It has to be taken into account, that the handful of studies on subliminal processing of pain-related stimuli used different stimuli and some also different paradigms which makes drawing conclusions difficult [9][10][11][12]. Beyond the fact that these studies had contradictory findings, two studies measured attentional interference (using a Stroop task) instead of attention towards a location, i.e., orienting towards a stimulus [9,10] which is a different aspect of attention, although related to AB [3,50].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Yet, research has shown that skinrelated disgust plays a role for patients with chronic skin diseases, so a relationship between attention to itch and disgust seems plausible [49] Nevertheless, the cumulative evidence for a preconscious AB towards-or avoidance of threat related stimuli like itch or pain is limited. It has to be taken into account, that the handful of studies on subliminal processing of pain-related stimuli used different stimuli and some also different paradigms which makes drawing conclusions difficult [9][10][11][12]. Beyond the fact that these studies had contradictory findings, two studies measured attentional interference (using a Stroop task) instead of attention towards a location, i.e., orienting towards a stimulus [9,10] which is a different aspect of attention, although related to AB [3,50].…”
Section: Plos Onementioning
confidence: 99%
“…These analyses showed significant attentional bias towards pain for conscious processing between 500-1000ms, while there is limited evidence for shorter(<500ms) or longer presentation times (>1000ms) [1,8]. However, this might also be due to a very limited amount of studies, especially in the preconscious processing range [9][10][11][12].…”
Section: Introductionmentioning
confidence: 97%
“…Following this, mean response times will be computed for each participant, with any response >3 SD from their individual mean also removed as outliers. This process ensures extremely quick or slow responses do not unduly bias the results, which are typically removed when cleaning and screening visual-probe data in pain-related research (eg, refs 18 64–67). An attentional bias index will then be computed for each stimulus and presentation time condition using the following equation: (TuPl−TlPl)+(TlPu−TuPu)/2.…”
Section: Methods and Analysismentioning
confidence: 99%